Food Insecurity, Quality of Life, and Diet Optimization of Low Income University Students in Selangor, Malaysia - Rajikan, R; Shin, LH; Hamid, NIA; Elias, SM (Bogor Agricultural Univ, Dept Community Nutrition, Fac Human Ecology, 2024)
Indexed by WOS